Impact of intra-aortic balloon counterpulsation on all-cause mortality among patients with Takotsubo syndrome complicated by cardiogenic shock: results from the German-Italian-Spanish (GEIST) registry. Issue 1 (24th January 2023) - Santoro, Francesco; Núñez Gil, Iván J; Stiermaier, Thomas; El-Battrawy, Ibrahim; Moeller, Christian; Guerra, Federico; Novo, Giuseppina; Arcari, Luca; Musumeci, Beatrice; Cacciotti, Luca; Mariano, Enrica; Romeo, Francesco; et al.
Abstract: Aims: Takotsubo syndrome (TTS) is an acute and reversible left ventricular dysfunction and can be complicated by cardiogenic shock (CS). However, few data are available on optimal care in TTS complicated by CS. Aim of this study was to evaluate short- and long-term impact of intra-aortic balloon pumping (IABP) on mortality in this setting. Methods and results: In a multi-centre, international registry on TTS, 2248 consecutive patients were enrolled from 38 centres from Germany, Italy, and Spain. Of the 2248 patients, 212 (9.4%) experienced CS. Patients with CS had a higher prevalence of diabetes (27% vs. 19%), male sex (25% vs. 10%), and right ventricular involvement (10% vs. 5%) ( P < 0.01 in all cases). Forty-three patients with CS (20% of 212) received IABP within 8 h (interquartile range 4–18) after admission. No differences in terms of age, gender, cardiovascular risk factors, and admission left ventricular ejection fraction were found among patients with and without IABP. There were no significant differences in terms of 30-day mortality (16% vs. 17%, P = 0.98), length of hospitalization (18.9 vs. 16.7 days, P = 0.51), and need of invasive ventilation (35% vs. 41%, P = 0.60) among two groups: 30-day survival was not significantly different even after propensity score adjustment (log-rank P = 0.73). At 42-month follow-up, overall mortality in patients with CS and TTS was 35%, not significantly different between patients receiving IABP and not (37% vs. 35%, P = 0.72). Conclusions: In a large multi-centre observational registry, the use of IABP was not associated with lower mortality rates at short- and long-term follow-up in patients with TTS and CS. Graphical Abstract: Graphical abstract Mechanical support with intra-aortic balloon pumping (IABP) in patients with Takotsubo syndrome and cardiogenic shock was not associated with survival benefit at short- and long-term mortality.